PENGARUH SEGMENTASI PASAR TERHADAP VOLUME PENJUALAN PRODUK JASA ASURANSI PT. AXA LIFE INDONESIA CABANG LAMPUNG - Yudiana Sari (Industrika : Jurnal Ilmiah Teknik Industri, 2019)
The object of this research is PT. Axa Life Indonesia Bandar Lampung Branch. The new slogan used by PT. Axa Life Indonesia "redifining / standards" reflects the desire to be the brand chosen by the public. To understand that people's choices are closely related to their trust in the insurance and financial services industry. The problem under study is wanting to know the effect of market segmentation on the sales volume of PT. Axa Life Indonesia Lampung Branch due to declining sales volume. The research method used in this study is library research and field research conducted by directly examining PT. Axa Life Indonesia Lampung Branch. The results showed that the effect of market segmentation on the sales volume of PT. Axa Life Indonesia Lampung Branch there is a high closeness relationship between the implementation of behavior segmentation with the sales volume of PT. Axa Life Indonesia Bandar Lampung Branch. This is based on the results of calculations through the Kendall Concordation test (W), it is known that there is a high closeness relationship between the implementation of behavior segmentation with the sales volume of PT. Axa Life Indonesia Bandar Lampung Branch. Significant test obtained by calculating X2 value of 162.8 by using critical prices of X2 as a reference, at various levels of alpha can be seen X2 count> X2 table. This means that Ho is rejected and Ha is accepted so it is proven that there is a high closeness relationship between the implementation of behavior segmentation with the sales volume of PT. Axa Life Indonesia Bandar Lampung Branch. In behavior segmentation, it can be seen a qualitative analysis of grouping of buyers based on the expected variables of benefits, price sensitivity, loyalty, and knowledge. Keywords: Segmentation, Sales, Products, Services, Marketing